Exploring Vocabulary Patterns through Digital Humanities: A Comparative Tool-Based Study on Arundhati Roy’s Novels - K., Thirumoorthi; V., Thamil Selvi (Recent Research Reviews Journal, 2025)
Vocabulary analysis is a valuable tool in literary studies, particularly when examining complex texts with layered meanings. The emergence of Digital Humanities has significantly simplified the process of vocabulary analysis. These digital tools assist researchers in identifying vocabulary, visualising vocabulary patterns, tracking changes across text, checking readability, monitoring repetition and lexical density, and comparing large textual units efficiently. Vocabulary serves as a structural and symbolic thread in literary texts, and Digital Humanities tools provide new avenues for tracing this thread. By bridging the gap between traditional literary methods and digital analysis, there is scope for enhanced understanding of narrative voice and the linguistic fabric of fiction. The deliberate repetition of specific terms or phrases often signals larger concerns within the narrative. This paper focuses on two accessible Digital Humanities tools, Voyant Tools and Online-Utility.org, which need not be installed but can be used free online. It also explores how these tools aid vocabulary analysis for literary interpretation. Further, these platforms enable researchers to explore how certain words recur across different narrative segments or in relation to particular characters or events, offering insights into the symbolic frameworks of texts. The novels The God of Small Things and The Ministry of Utmost Happiness by Arundhati Roy are used to explore vocabulary. It specifies the best tool for better literary support without coding knowledge in navigating the intricacies of vocabulary and achieving deeper textual insights.